Bending Pyrenacenes to Fill Gaps in Singlet-Fission-Based Solar Cells - Cruz, Carlos M.; Walsh, Joshua C.; Juríček, Michal (Organic Materials, 2022)
Singlet fission is envisaged to enhance the efficiency of single-junction solar cells beyond the current theoretical limit. Even though sensitizers that undergo singlet fission efficiently are known, characteristics like low-energy triplet state or insufficient stability restrict their use in silicon-based solar cells. Pyrenacenes have the potential to overcome these limitations, but singlet-fission processes in these materials is outcompeted by excimer formation. In this work, bent pyrenacenes with a reduced propensity to stack and thus form excimers are computationally evaluated as singlet-fission materials. The energies of the S1, T1 and T2 states were estimated in a series of bent pyrenacenes by means of time-dependent density functional theory calculations. Our results show the opposite trend observed for perylene diimides, namely, an increase in the energy of the T1 and S1 states upon bending. In addition, we show that the energy levels can be tuned on demand by manipulating the bend angle to match the energy gap of various semiconductors that can be used in single-junction solar cells, making pyrenacenes promising candidates for singlet fission.
Keywords: bent polycyclic aromatic hydrocarbons; density functional theory; pyrenacenes; ropyrenes; rylene diimides; singlet fission